Analisis Laporan Arus Kas Pada PT Pos Persero Cabang Bima - Megasuciati Wardani (AKUNTANSI 45, 2022)
The purpose of this research is to determine the Cash Flow at PT POS Persero Bima Branch. The type of research used in the research is descriptive research. Data collection techniques in this research are observation, documentation, interviews and literature study. Meanwhile, the data analysis technique in this research is through financial analysis. Analyzing cash flow reports at PT. POS Persero Bima Branch, namely the Operating Cash Flow Ratio, calculates the ability of operating cash flow to pay obligations smoothly. This ratio is obtained by dividing operating cash flow by current liabilities. The Cash Flow Report at PT POS Persero Bima Branch is below the AKO Ratio standard of 1, which reflects that PT POS Persero’s cash position is still not safe to meet its current obligations. Where by using the one sample t test, the calculated t value is smaller than the t table value, so that what is accepted is an alternative hypothesis, namely the assumption that the Operating Cash Flow Ratio (AKO) of PT POS Persero Bima Branch is below the standard AKO Ratio. The results of the one sample t test obtained a t value of -75.084 and a t table of 1.533. By comparing the tcount and ttable values, it turns out that the tcount value is greater than ttable (-75.084<1.533). So the alternative hypothesis (Ha) which reads "It is suspected that the Operating Cash Flow Ratio (AKO) at PT POS Persero Bima Branch is equal to or more than 1". cannot be accepted/rejected